2018
DOI: 10.1192/bjo.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Trends in female authorship in research papers on eating disorders: 20-year bibliometric study

Abstract: BackgroundThere is a clear gender gap in scientific authorship. Although the proportions of female authors in medicine and psychiatry have increased over the past decades, women are still underrepresented.AimsTo analyse authorship gender trends in eating disorder research.MethodFirst and last author gender in research articles on eating disorders during the period 1997–2016 were assessed in eating disorder specialty journals, high-impact psychiatry journals and high-impact clinical psychology journals.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 55 publications
1
21
1
Order By: Relevance
“…Overall, we find that the representation of women among authors did not vary with journal impact factor (Figure ). This contrasts with previous findings from mathematics (Mihaljević‐Brandt, Santamaría, & Tullney, ), biology journals more generally (Bonham & Stefan, ), journals in the Nature Index (Bendels, Müller, Brueggmann, & Groneberg, ), and in biomedical journals (Shen, Webster, Shoda, & Fine, ; Strand & Bulik, ), all of which showed that women were less well represented as authors in higher impact factor journals (though this pattern was not seen for computational biology journals; Bonham & Stefan, ). Those previous studies also generally find that women are less well represented at the more prestigious authorship positions in high impact factor journals than in lower impact factor journals, a pattern we did not observe.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, we find that the representation of women among authors did not vary with journal impact factor (Figure ). This contrasts with previous findings from mathematics (Mihaljević‐Brandt, Santamaría, & Tullney, ), biology journals more generally (Bonham & Stefan, ), journals in the Nature Index (Bendels, Müller, Brueggmann, & Groneberg, ), and in biomedical journals (Shen, Webster, Shoda, & Fine, ; Strand & Bulik, ), all of which showed that women were less well represented as authors in higher impact factor journals (though this pattern was not seen for computational biology journals; Bonham & Stefan, ). Those previous studies also generally find that women are less well represented at the more prestigious authorship positions in high impact factor journals than in lower impact factor journals, a pattern we did not observe.…”
Section: Discussioncontrasting
confidence: 99%
“…Most visible indicator of gender disparities in health scientific research is the number of publications in indexed journals. Medical articles produced by women has grown significantly [68], however there is still a substantial gender gap [912], where women produce a third of medical articles worldwide [13]. Several factors can explain this gap [68].…”
Section: Introductionmentioning
confidence: 99%
“…Medical articles produced by women has grown significantly [68], however there is still a substantial gender gap [912], where women produce a third of medical articles worldwide [13]. Several factors can explain this gap [68]. Most studies highlight the presence of observable factors that disadvantage women, such as barriers in access to resources and academic opportunities, as well as cultural norms that overcharge home chores for women, especially in child care responsibilities [1419].…”
Section: Introductionmentioning
confidence: 99%
“…case analysis with literature review 14 • Trends in female authorship in research papers on eating disorders: 20-year bibliometric study 15 • The prevalence and treatment outcomes of antineuronal antibody-positive patients admitted with first episode of psychosis 16 • Mother and baby units matter: improved outcomes for both 17 • Suicide attempts and non-suicidal self-harm: national prevalence study of young adults 18 • Association between suicidal ideation and suicide: meta-analyses of odds ratios, sensitivity, specificity and positive predictive value 19 • Predicting major mental illness: ethical and practical considerations 20 • Indirect costs of depression and other mental and behavioural disorders for Australia from 2015 to 2030 21 • Social gradients in the receipt of medication for attention-deficit hyperactivity disorder in children and young people in Sheffield 22 • Long-term subjective memory after electroconvulsive therapy 23 The breadth of published articles ranges from treatment efficacy to adverse effects, from nonadherence to social gradients in prescriptions, from forensic psychiatry to mental health law, from ethics to global mental health, from history of terminology to guidelines, from digital mental health to determination of value and healthcare economics, from neuropsychiatry to perinatal psychiatry, from stigma to quality of life…and the list goes on.…”
Section: What We Have Accomplishedmentioning
confidence: 99%